Preflight Detector Characterization of BLAST-TNG - Gordon S.; Sinclair A.; Mauskopf P.; Coppi G.; Devlin M.; Dober B.; Fissel L.; Galitzki N.; Gao J.; Hubmayr J.; Lourie N.; Lowe I.; et al. (Journal of Low Temperature Physics, 2020)
The Next-Generation Balloon-borne Large-Aperture Submillimeter Telescope (BLAST-TNG) is a submillimeter imaging polarimeter which will map the polarized thermal emission from interstellar dust, revealing magnetic field structures in nearby giant molecular clouds, external galaxies and the diffuse interstellar medium in three bands centered at 250, 350 and 500-μm (spatial resolution of 30′′, 41′′ and 59′′). Its camera contains over 2500 dual-polarization sensitive lumped element kinetic inductance detectors, which are read out using field-programmable gate array-based readout electronics. BLAST-TNG was scheduled for a 28-day Antarctic flight during the 2018/2019 summer season, but unfavorable weather conditions pushed the anticipated flight to 2019/2020. We present a summary of key results from the 2018/2019 preflight characterization of the detector and receiver. Included in this summary are detector yields, estimates of in-flight sensitivity, a measurement of the optical passbands and estimates of polarization efficiency.